MENELUSURI DINAMIKA INKULTURASI DAN AKULTURASI ETNIS BOLAANG MONGONDOW DI SULAWESI UTARA - Marde Christian Stenly Mawikere; Sudiria Hura (Pascasarjana IAKN Manado, 2020)
This study traces the Inculturation and Acculturation of Bolaang Mongondow Ethnics, one of the social groups in North Sulawesi. The elements of Inculturation studied consisted of History and Social Contexts, while the Elements of Acculturation studied consisted of the attitude of the Bolaang Mongondow People to Openness and Change. This study shows that the Bolaang Mongondow ethnic group has historically originated from the background of traditional societies who have a wealth of cultural arts and then by interaction and influence from outside communities have had an open attitude towards outsiders and change. Thus this study will contribute to and stimulate efforts in a comprehensive service and development approach, both physically, emotionally and spiritually as well as contextually for the Bolaang Mongondow ethnic group